Functional characterisation of the EgPAL5 promoter from oil palm (Elaeis guineensis Jacq.) reveals its potential roles in plant growth and adaptation to drought - Yusuf, Chong Yu Lok; Nawawi, Omar; Azhari, Mohd Farhan; Hilman, Mohamad Shafek; Bai, Tianqi; Zhang, Cuixian; Yi, Huaifeng; Ni, Zhangguang; Xie, Dehong; Abdullah, Meilina Ong; Abdul Masani, Mat Yunus; Shaharuddin, Noor Azmi; et al. (Taylor and Francis, 2025)
Oil palm (Elaeis guineensis) is a globally important oil crop whose genome contains five phenylalanine ammonia lyase (EgPAL) genes. In this study, we characterised the regulatory architecture of the EgPAL5 promoter by generating transgenic plants carrying the EgPAL5 promoter fused to GUS. We first conducted an in silico analysis of the 2.3 kb 5’ flanking region, identifying multiple cis-regulatory motifs involved in monolignol biosynthesis, osmotic stress response, and hormone signalling. Reporter assays under normal growth conditions revealed broad promoter activity throughout the seedling and adult plant, with developmental modulation manifested as higher GUS expression detected in expanding leaves and developing siliques. Under simulated drought stress, GUS activity increased markedly, indicating strong promoter induction. Moreover, overexpression of the Arabidopsis AtMYB58 transcription factor significantly enhanced EgPAL5 promoter activity, further implying that the EgPAL5 promoter was responsive to regulatory cues associated with lignin biosynthesis. Promoter deletion mapping localised essential cis-elements required for full transcriptional activity to the −1033 to −651 bp region upstream of the transcription start site. Together, these results demonstrate that the EgPAL5 promoter integrates developmental cues and environmental stimuli to modulate phenylpropanoid metabolism.